A rare case of Bezold’s abscess presenting as parapharyngeal abscess - Bihani, Ameya; Dabholkar, Jyoti P. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2015)
Bezold’s abscess is a very rare complication of unsafe chronic suppurative otitis media. The diagnosis of Bezold’s abscess is clinched by the presence of inflammation which is tracking down the anterior belly of digastrics and sternocleidomastoid. Surgery constituting incision and drainage of abscess with canal wall modified radical mastoidectomy is treatment of choice. We hereby present a case of 42 year male presenting with parapharyngeal abscess (Bezold’s abscess) which was secondary to unsafe chronic suppurative otitis media.